Analysis of differences in prion protein gene (PRNP) polymorphisms between Algerian and Southern Italy's goats. Issue 3 (3rd July 2018) - Fantazi, Khaled; Migliore, Sergio; Kdidi, Samia; Racinaro, Luca; Tefiel, Hakim; Boukhari, Rachid; Federico, Giovanni; Di Marco Lo Presti, Vincenzo; Gaouar, Semir Bechir Suheil; Vitale, Maria
Abstract: Goats are adapted to live in harsh areas of the world ensuring minimum levels of milk and meat production without much economic input. Scrapie is a fatal prion disease of small ruminants detected in different countries worldwide. Polymorphisms in the prion protein gene ( PRNP ) modify the degree of susceptibility/resistance to scrapie. PRNP polymorphisms were analysed in the four main Algerian goat breeds ( Naine de Kabylie, Arbia, Mozabite, Mekatia ), and in two native breeds of South Italy ( Aspromontana from Calabria and Cilentana from Campania). The results were compared also with two previously described Sicilian native breeds ( Girgentana and Rossa Mediterranea ). Seven amino acid substitutions were detected in Naine de Kabylie goat which represents the original native Berber breed. All other breeds presented no more than six variants and common polymorphisms were present at codons, 154 and 240. Isoleucine at 137 was present in Algerian breeds only. The Italian Cilentana shared more variants with Algerian breeds whereas the Aspromontana breed was the only one to show a Serine at 127. Exclusive new variants were not detected since all polymorphisms were already described in other goats worldwide. The scrapie protective allele encoding lysine (K) at codon 222 was detected in the Naine de Kabylie and M'zabite breeds at low-frequency whereas is present with frequencies higher than 10% in all the Italian breeds reared in regions with elevated scrapie incidence. The overall results showed a substantial number of polymorphisms in PRNP, particularly in Naine de Kabylie breed, which carried also unique genotypes.